Adrenal Hemangioma Definite Diagnosis on CT, MRI, and FDG PET in a Patient With Primary Lung Cancer. (June 2018) - Wilson, Benjamin; Becker, Allison; Estes, Thomas; Keshavamurthy, Jayanth; Pucar, Darko
Abstract : Abstract: Distinguishing adrenal incidentalomas (5% of all abdominal CT scans) from metastasis is a frequent diagnostic challenge in primary malignancies with a propensity for adrenal spread, such as lung cancer. Adrenal myelolipoma and adenoma can be definitively characterized as benign by demonstrating gross and microscopic fat, respectively, on CT and MRI and an absence of abnormal uptake on PET. Unfortunately, adrenal sampling is frequently necessary in indeterminate cases for adequate staging of extra-adrenal primary malignancy. We present a lung cancer case in which definite characterization of a rare adrenal hemangioma with CT, PET, and MRI avoided unnecessary adrenal sampling.